Reobserving the Term of the Táqat (the Strength) in the Sawm (Fast) Verse - Muhammad Mahdi Masoudi (آموزه‌های قرآنی)
Knowledge of the literature of the time of the revelation is inevitable to understand the Quran. Perhaps some terms were used (well known) during the time of the revelation in the meanings but with the passing of the time they have been evolved. One of these words which makes the commentators confront problems is “ Táqat” (the strength) which they have rendered different translations. The realm of these polarities is not limited to the translations but includes the interpretations. Meanwhile, this paper reobserves the Sawm (Fast) Verse; it has mentioned the semantic of the term of "Táqat" and its role in the verse concept.